Marcus kinetics control singlet and triplet oxygen evolving from superoxide - Soumyadip Mondal; Huyen T. K. Nguyen; Robert Hauschild; Stefan A. Freunberger (Nature, 2025)
Abstract Oxygen redox chemistry is central to life1 and many human-made technologies, such as in energy storage2–4. The large energy gain from oxygen redox reactions is often connected with the occurrence of harmful reactive oxygen species3,5,6. Key species are superoxide and the highly reactive singlet oxygen3–7, which may evolve from superoxide. However, the factors determining the formation of singlet oxygen, rather than the relatively unreactive triplet oxygen, are unknown. Here we report that the release of triplet or singlet oxygen is governed by individual Marcus normal and inverted region behaviour. We found that as the driving force for the reaction increases, the initially dominant evolution of triplet oxygen slows down, and singlet oxygen evolution becomes predominant with higher maximum kinetics. This behaviour also applies to the widely observed superoxide disproportionation, in which one superoxide is oxidized by another, in both non-aqueous and aqueous systems, with Lewis and Brønsted acidity controlling the driving forces. Singlet oxygen yields governed by these conditions are relevant, for example, in batteries or cellular organelles in which superoxide forms. Our findings suggest ways to understand and control spin states and kinetics in oxygen redox chemistry, with implications for fields, including life sciences, pure chemistry and energy storage.